2019
DOI: 10.1016/j.jfda.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive HPLC-FLD method combined with multivariate analysis for the determination of amino acids in l-citrulline rich vegetables

Abstract: The proposed analytical method reports the separation and quantification of 21 amino acids including l -citrulline from fresh vegetables and commercial juices using a C 8 column. Optimal separation conditions for amino acids analysis were obtained with 20 mM sodium acetate (solvent A) and water with organic modifier acetonitrile and methanol (solvent B; 18/50/32 V/V). The ideal pH and column temperature were found to be 5.40 and 35 °C, respectively. The LOD and LOQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Melon varieties CRU (IN) and ALG (AZ) had significantly higher levels of Cit at 360.52 ± 23.49 and 307.33 ± 58.84 µg/g, respectively, than the other varieties harvested from different locations. Citrulline, a non-essential amino acid and precursor to the arginine, is mainly present in Cucurbitaceae family members such as watermelon, squash, and cucumber [ 5 ]. A recent study reported the effect of two growing locations in NC on Cit and Arg levels, using different cultivars from those we studied here.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Melon varieties CRU (IN) and ALG (AZ) had significantly higher levels of Cit at 360.52 ± 23.49 and 307.33 ± 58.84 µg/g, respectively, than the other varieties harvested from different locations. Citrulline, a non-essential amino acid and precursor to the arginine, is mainly present in Cucurbitaceae family members such as watermelon, squash, and cucumber [ 5 ]. A recent study reported the effect of two growing locations in NC on Cit and Arg levels, using different cultivars from those we studied here.…”
Section: Resultsmentioning
confidence: 99%
“…Melon fruits have high levels of the GABA [ 3 ] and other amino acids, particularly valine and alanine [ 4 ]. Amino acid identification and quantification of melon can be performed by reverse phase liquid chromatography, gas chromatography, and nuclear magnetic resonance [ 5 , 6 , 7 ]. Liquid chromatography is a commonly used technique for analysis of amino acids from plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the most common labelling reagents used for post- and pre-column derivatization are ninhydrin and o-phthaldialdehyde (OPA), 6-aminoquinolyl-N-hydroxysuccinimidyl carbamate (AQC), phenylisothiocyanate (PITC) and 9-fluorenylmethyl chloroformate (FMOC) respectively [ 160 ]. However, there was a report of using OPA as pre-column derivatization to enhance sensitivity for fluorescent detection [ 137 ]. Derivatization process was made easier and simpler when using AQC as it is stable at room temperature for several days, has low toxicity, fewer side reactions and takes a shorter time to complete [ 143 ].…”
Section: Amino Acidsmentioning
confidence: 99%
“…Suppression of different microorganisms is manifested even at small concentrations of acetic acid (0.2-0.3 % of acid of the total mass of pickled products). At small concentration 0.4-0.6 % of acetic acid subacid marinades, not stable at storage, form [1][2][3][4][5]. As a result of the small concentration of vinegar, microorganisms in such marinades are partially suppressed, their essential part can develop and cause spoilage of the product.…”
Section: Introductionmentioning
confidence: 99%